2019
DOI: 10.3390/su11215951
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Cropland Abandonment in Mountainous Areas Using an Annual Land-Use Trajectory Approach

Abstract: In recent years, with the unceasing acceleration of China's urbanization and rapid development of the country's economy, cropland abandonment has become an ongoing issue, especially in mountainous areas. Mapping abandoned cropland using remote sensing technology is still challenging due to the difficulties in distinguishing abandoned cropland from fallowed land. In addition, there are few credible approaches to map timing and recultivation of abandoned cropland. In this context, this research developed an annu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 60 publications
0
11
1
Order By: Relevance
“…(1) ALS data allowed for an automated and more accurate identification of AAL in terms of classification accuracy (>90%) and spatial resolution (<1.0 m) than did other RS platforms [53][54][55][56][57][58][59][60][61][62][63][64]. Potential improvements in process of AAL identification may be achieved using some qualitative variable of ALS data (e.g., intensity) or alternatively through multispectral ALS data [65][66][67][68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) ALS data allowed for an automated and more accurate identification of AAL in terms of classification accuracy (>90%) and spatial resolution (<1.0 m) than did other RS platforms [53][54][55][56][57][58][59][60][61][62][63][64]. Potential improvements in process of AAL identification may be achieved using some qualitative variable of ALS data (e.g., intensity) or alternatively through multispectral ALS data [65][66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…This is because they are generally more accessible for large areas than ALS data. Here, an application of spectral or multiscale features extracted from aerial [60] or satellite images, such as GF-2 [61], Quick Bird [62], and Landsat [63], resulted in an overall accuracy of 77-91%. Several studies have also demonstrated the potential of radar data as an alternative to optical images for the identification of AAL.…”
Section: Spatial Identification Of Abandoned Agricultural Landmentioning
confidence: 99%
“…Landsat time series data has a high spatial resolution (30 m), which has a great advantage in identifying finely fragmented abandoned land in mountainous areas. For example, Song [24] mapped the trajectory of land use change based on Landsat and HJ-1 satellite images, and mapped different types of cropland abandoned in the town of Zhongduo, Chongqing from 2012 to 2017. However, due to the remote sensing image acquisition time and cloud influence, the acquisition of long time series data was limited.…”
Section: Introductionmentioning
confidence: 99%
“…Scientist Wei Song wrote that two types of approaches have been adopted to estimate the scale of cropland abandonment in previous research: Household surveys and remote sensing monitoring [4]. Freely accessible satellite images have provided many data sources to map abandoned croplands.…”
Section: Introductionmentioning
confidence: 99%
“…Freely accessible satellite images have provided many data sources to map abandoned croplands. Based on the spatial resolution of satellite images, the Moderate Resolution Imaging Spectroradiometer (MODIS), Landsat, and high-resolution satellite data, such as Quick-Bird, and aerial photographs are generally adopted to identify abandoned croplands [4]. Most countries, including Lithuania, have mosaics of multispectral terrestrial satellite imagery (Sentinel-2 satellite) of their territory, which are ready for analysis and research.…”
Section: Introductionmentioning
confidence: 99%